Development of a Synthetic Medium to Investigate the Role of Buffer Capacity and Metabolites on the Fermentation Chemistry of Cucumber Juice - Allison Anthony; Caitlin Skinner; Neeraj Katare; David Guydan; Suzanne Johanningsmeier; Fred Breidt (Journal of Food Protection)
The objective of this study was to investigate the role of buffer capacity in the fermentation biochemistry of a model cucumber fermentation system. To this end, synthetic media were prepared that had similar fermentation properties to cucumber juice (CJ). While synthetic media are commonly used, matching the buffer capacity of a natural microbial fermentation with a synthetic medium has not been attempted. Buffer modeling technology has recently been shown to be an effective means to link pH and weak acid concentration in acid and acidified foods. Our hypothesis was that an artificial cucumber juice medium (ACJ) with similar buffering and nutrients to CJ would result in similar metabolite and pH changes during fermentation by Lactiplantibacillus pentosus LA445 (a commercial cucumber fermentation isolate). ACJ formulations (N = 27) were prepared based on the composition of 10 independent CJ preparations. Selected ACJ formulations that had similar buffer capacities to CJ preparations in the pH 2–7 range were fermented under anaerobic conditions. Malic acid was found to be the principal buffer in this pH range, and the initial concentration correlated with sugar utilization and final medium pH. The data showed that media with similar buffer capacity resulted in similar sugar utilization (p > 0.05) following 72 h of fermentation. The data indicate that artificial media developed with buffer modeling technology may be useful for the study of a variety of food and other fermentations to control pH evolution and acid production, which influence quality and safety.